Development Of A Novel T/A Cloning And Expression Vector For Efficient Expression Of Protein-Based Biopharmaceuticals In Escherichia Coli - Che Nordin, Muhamad Alif (2017)
Escherichia coli is one of the most popular bacterial hosts for handling, manipulating, and expressing target genes of interest. Certain genes are difficult to express, often due to scarcity of specific tRNA. This has led to little and/or poor quality protein production in E. coli. To alleviate this problem, E. coli hosts are transformed with rare tRNA-expressing helper plasmid vectors. Maintenance of two different plasmid vectors-expressing the gene of interest and rare tRNA genes exert metabolic burden on the host that may result in diminished growth and reduced protein production.